2020
DOI: 10.2196/17744
|View full text |Cite
|
Sign up to set email alerts
|

The Promise of Patient Portals for Individuals Living With Chronic Illness: Qualitative Study Identifying Pathways of Patient Engagement

Abstract: Background Patients play a critical role in managing their health, especially in the context of chronic conditions like diabetes. Electronic patient portals have been identified as a potential means to improve patient engagement; that is, patients’ involvement in their care. However, little is known about the pathways through which portals may help patients engage in their care. Objective Our objective is to understand how an electronic patient portal f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Although we should be cautious in interpreting the relationship between using patient portals and self-efficacy as causal, we did observe a co-occurrence of better outcomes and increased patient portal usage intensity. Despite the benefits of patient portals being well documented [ 39 , 40 ], rates of usage remain low [ 41 ], and increasing the adoption of patient portals would provide more patients a trusted source of personalized information. Because patients can be easily misinformed by the large amount of inaccurate information online [ 42 ], using patient portals allows patients and their caregivers to stay connected with their providers.…”
Section: Discussionmentioning
confidence: 99%
“…Although we should be cautious in interpreting the relationship between using patient portals and self-efficacy as causal, we did observe a co-occurrence of better outcomes and increased patient portal usage intensity. Despite the benefits of patient portals being well documented [ 39 , 40 ], rates of usage remain low [ 41 ], and increasing the adoption of patient portals would provide more patients a trusted source of personalized information. Because patients can be easily misinformed by the large amount of inaccurate information online [ 42 ], using patient portals allows patients and their caregivers to stay connected with their providers.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, we focused on secure messaging because it improves patients' access to their clinicians by offering a convenient mechanism for patient‐clinician communication for patients comfortable with this communication modality 1 . Further, both clinicians and patients support secure messaging as a useful and valuable communication modality 3,6,84‐92 . Given that secure messaging accounts for a growing and significant portion of patient‐clinician outpatient encounters, 4,5 the application of our taxonomy provides important insights into (1) patients' use of this modality to self‐manage their condition and address their uncertainty, and (2) how clinicians' responses to patients through this mechanism incorporate communication functions associated with promoting patients' indirect and health outcomes 93 …”
Section: Discussionmentioning
confidence: 99%
“…40,41 Research has found that relationship building is possible through technology-mediated communication like secure messaging. 6,[42][43][44][45]…”
Section: Theoretical Contextmentioning
confidence: 99%
See 2 more Smart Citations